Перспективи підвищення ефективності обробки складнопрофільних виробів із крихких неметалевих матеріалів - Калафатова, Л. П. (Національний технічний університет "Харківський політехнічний інститут", 2019)
Визначені шляхи підвищення ефективності шліфування виробів – оболонок складної форми з кераміки і ситалів, що пов’язані із забезпеченням вібростійкості технологічної системи обробки. Для конкретних умов завдяки використанню розробленої узагальненої математичної моделі формування похибки профілю при механічній обробці встановлені пріоритетні напрямки підвищення жорсткості елементів технологічної системи, серед яких провідне значення мають конструкція заготовки, недоліки технології заготівельних операцій і особливості використаних верстатних систем. Для вирішення завдання запропоновано удосконалення існуючої технології отримання заготовки; перехід на оброку оболонок на верстатах х ЧПК; можливість використання технології 3D-друку при виробництві точних складнопрофільних деталей з кераміки.

There are certain requirements to the quality of profile-composite thin-walled shells used in aerospace engineering. All the necessary characteristics of the items (such as thickness of shells, profile accuracy and surface quality) can be provided using the method of diamond grinding. Therefore, the researches, related to establishing an analytical connection between the phenomena arising during tooling of such wares and errors of their form and geometry, are relevant. The purpose of these research is to determine the direction of increasing the vibration-resistance of the grinding system by improving the workpiece production technology, which ensures the approximation of the size and geometry of the workpiece (the main element of the grinding system) to the same parameters of the workpiece. The performed researches allowed to develop a generalized mathematical model of formation of total error of the profile of a thin-walled pyroceram shell considering factors influencing the level of vibrations of elements of the grinding technological system and the accuracy of treatment. The model considers the unevenness of the allowance, which occurs at the stage of obtaining the workpiece, as well as the variable stiffness of the workpiece and the machine tool. Priority directions of increasing the stiffness of the elements of the technological system are established. Among them of the leading importance are the construction of the workpiece, the drawbacks of the workpiece production technology and the features of machine systems using. For the solution of the problem, we proposed: improving the existing workpiece production technology; transition to machining on CNC machines; the possibility of using 3D printing technology in the production of precise complicated parts from ceramics.
Perspectives for improving the efficiency of machining of complex profiles products from brittle non_metallic materials
Keywords: технічна кераміка; тонкостінні оболонки; алмазне шліфування; динаміка процесу; technical ceramics; thin-walled shell; diamond grinding; dynamics of process